2021
DOI: 10.1128/mbio.01049-21
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Essentiality Analysis of Mycobacterium abscessus by Saturated Transposon Mutagenesis and Deep Sequencing

Abstract: Limited knowledge regarding Mycobacterium abscessus pathogenesis and intrinsic resistance to most classes of antibiotics is a major obstacle to developing more effective strategies to prevent and mitigate disease. Using optimized procedures for Himar1 transposon mutagenesis and deep sequencing, we performed a comprehensive analysis to identify M. abscessus genetic elements essential for in vitro growth and compare them to similar data sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 104 publications
10
40
0
Order By: Relevance
“…We found that MAB_3167c lacked transposon insertions across all three replicate libraries (Figure 3A). This finding corroborates data from previously generated Mab transposon libraries that show lack of insertions in MAB_3167c (10, 12). Comparing the essentiality of PBP enzymes in Mab with their homologs in Mtb revealed that MAB_3167c is unique in being the sole PBP whose essentiality differs between the two species.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We found that MAB_3167c lacked transposon insertions across all three replicate libraries (Figure 3A). This finding corroborates data from previously generated Mab transposon libraries that show lack of insertions in MAB_3167c (10, 12). Comparing the essentiality of PBP enzymes in Mab with their homologs in Mtb revealed that MAB_3167c is unique in being the sole PBP whose essentiality differs between the two species.…”
Section: Resultssupporting
confidence: 92%
“…Overall, the newly generated Mab transposon libraries can be used to determine genes required for growth in a variety of conditions including infection models, biofilms, and antibiotic stress. Both Rifat et al’s and our TnSeq data identified PBP-lipo as the sole PBP that is essential in Mab and non-essential in Mtb (12). Using CRISPRi, we demonstrated the necessity of PBP-lipo expression for Mab to maintain normal morphology and to divide properly.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The predictive power of our model on the M. abscessus data set ( R 2 of 0.504) is slightly higher than, but about the same as, the M. tuberculosis test set. We ran the same analysis on a recently published TnSeq data set from an independent library of M. abscessus ATCC 19977 ( 16 ) as well and observed very similar heatmaps and predictive power ( R 2 of 0.477). This shows we can explain ∼50% of the variance in Himar1 insertion counts in this organism based on the nucleotide biases.…”
Section: Resultsmentioning
confidence: 84%
“…Transposon insertion site mapping, using methods such as Tn‐seq or TraDIS, has been widely applied to study essentiality and fitness impact of genes in different organisms (Goodall et al, 2018; Rifat et al, 2021). This technique has also been extended to investigate synthetic interactions between genes via comparative analyses of transposon insertion site profiles in different strain backgrounds (Truong et al, 2020; Winkle et al, 2021).…”
Section: Resultsmentioning
confidence: 99%